PENDAMPINGAN SERTIFIKASI HALAL SKEMA SELF DECLARE PADA UMK DAPOER SISKA DI PUTAT LOR KABUPATEN MALANG - Noviyanti, Ririn (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2023)
Purpose of the study: The aim of this activity is to increase literacy regarding halal certification which can be done by self-declaration to MSMEs and assist business actors in submitting applications for halal certificates. Methodology: There are three stages in this service, namely the preliminary stage for identifying the character of the business; socialization and mentoring stages as the core of service activities; and evaluation stage. Main Findings: Business actors understand applying for certification using a self-declare scheme and follow the application process cooperatively. Applications of this study: This service is useful for MSMEs who wish to apply for a halal certificate through the self-declare scheme Novelty/Originality of this study: Increasing halal literacy and encouraging the issuance of halal certificates for business actors.